THE QUANTITATIVE RESEARCH ON 3-DIMENSIONAL SIMILARITY OF URBAN TEXTURE - N. C. Xiang; B. F. Ting; C. L. Xiaojun; D. L. Jing (Lowland Technology International, 2011)
Urban texture represents the city’s characteristics abstractly. Based on the study of city in three dimensional orientations and the figure-ground relation theory, an evaluation system on the building form in the city has been set up by bringing forward the conception of regional 3-dimensional (3D) density, 3D similarity, 3D contrast and regional spatial complexity. This paper is about 3D similarity as a part of the research series. The evaluation system describes the morphological distribution and the differences of scale between buildings in 6 sample sites through rational analysis using qualitative figures and quantitative calculations, verifying the consistency of quantitative calculation and experience.